Kontribusi Gaya Mengajar Guru terhadap Pembentukan Potensi Kognitif dan Emosional Siswa - Suprih Hartanto (Chalim Journal of Teaching and Learning, 2025)
This study aims to examine how teachers' teaching styles contribute to enhancing students' learning motivation both cognitively and emotionally. Utilizing library research and content analysis methods, this study reviews various literature and previous research related to teaching styles and their impact on students. The findings indicate that participatory, communicative, and active teaching approaches such as problem-based learning, cooperative learning, and inquiry-based learning significantly enhance students’ critical thinking, creativity, and emotional balance. Effective teaching styles also foster a conducive learning climate, strengthen emotional regulation, empathy, and students’ self-concept. Therefore, teaching strategies that holistically integrate cognitive and emotional aspects serve as a crucial foundation for creating transformative and sustainable education.